(untitled) (Conferencea, 2023)
This article discusses ample opportunities for aesthetic education of students through the spatial perception of geometric shapes, as well as proof of theorems and various methods and constructions used in solving many problems, learning the properties of shapes, modeling new configurations, the symmetry and beauty of regular polygons, the perfection of geometric patterns that teaching a geometric course in general education creates. All these are thought to be sources of intellectual development and aesthetic impact on students.